2023
DOI: 10.3389/fchem.2023.1121724
|View full text |Cite
|
Sign up to set email alerts
|

Lethal activity of BRD4 PROTAC degrader QCA570 against bladder cancer cells

Abstract: Bladder cancer is the most common malignancy of the urinary system. Efforts to identify innovative and effective therapies for bladder cancer are urgently needed. Recent studies have identified the BRD4 protein as the critical factor in regulation of cell proliferation and apoptosis in bladder cancer, and it shows promising potential for pharmacologic treatment against bladder cancer. In this study, we have evaluated the biological function of QCA570, a novel BET degrader, on multiple bladder cancer cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Furthermore, according to reports, there was an effective inhibition of the growth of non-small cell lung cancer (NSCLC) cells in humans and showed a synergistic effect with osimertinib for suppressing osimertinib-resistant EGFR-mutant NSCLC cells both in vitro and in vivo 13 . QCA570 also potently induced BRD4 degradation (DC 50 ≈ 1 nM) in several breast cancer cell lines at nanomolar concentrations 129 . The findings demonstrated a reduction in EZH2 and c-Myc levels via both transcriptional repression and protein degradation.…”
Section: Bromodomain-containing Proteins and Related Targetsmentioning
confidence: 97%
“…Furthermore, according to reports, there was an effective inhibition of the growth of non-small cell lung cancer (NSCLC) cells in humans and showed a synergistic effect with osimertinib for suppressing osimertinib-resistant EGFR-mutant NSCLC cells both in vitro and in vivo 13 . QCA570 also potently induced BRD4 degradation (DC 50 ≈ 1 nM) in several breast cancer cell lines at nanomolar concentrations 129 . The findings demonstrated a reduction in EZH2 and c-Myc levels via both transcriptional repression and protein degradation.…”
Section: Bromodomain-containing Proteins and Related Targetsmentioning
confidence: 97%
“…Moreover, as the earliest target of PROTAC application, BET protein degraders showed significantly stronger anti-proliferative activity than JQ1, indicating better anti-tumor activity of PROTAC technology compared with typical small molecules (Qin, Hu et al, 2018). ARV-825, MZ1, and dBET series compounds are BET protein inhibitors based on PROTAC technology, which are superior to traditional BET protein family inhibitors in selectivity, anti-tumor ability, and drug resistance to targets (Table 1) (Winter, 7 / 46 He, Zan et al, 2022;Liu, Qian et al, 2022;Peter, Eisenwort et al, 2022;Piya, Yang et al, 2022;Wang, Xu et al, 2022;Yang, Hu et al, 2022;Zhang, Peng et al, 2022;Zhang, Gao et al, 2022;He, Ju et al, 2023;Huang, Yao et al, 2023;Ivanov, Milosevic Feenstra et al, 2023;Kim, Choi et al, 2023;Liu, Chen et al, 2023;Rose, Fleming et al, 2023;Wang, Li et al, 2023). In addition, BET inhibitors have also been used in combination with AKT inhibitors, PARP inhibitors, and BCL-2 inhibitors, demonstrating impressive therapeutic effects on tumors (Bevill, Olivares-Quintero et al, 2019;Tian, Chen et al, 2019;Fehling, Miller et al, 2020;Lee, Kang et al, 2020;Shigeta, Lui et al, 2021;Zhang, Cai et al, 2021).…”
Section: Classification and Structure Of Bet Protein Familymentioning
confidence: 99%
“…One study has shown that one BET (bromodomain and extraterminal domain) inhibitor mivebresib synergized with a Bcl-xL PROTAC degrader PZ703b increased cell apoptosis through the mitochondrial pathway in bladder cancer (177). Another study showed that BRD4 PROTAC degrader QCA570 increased the degradation of BRD4 protein, leading to induction of cell apoptosis and cell cycle arrest, which caused antiproliferation ability in bladder cancer (178). All in a word, E3 ubiquitin ligases are essential for the initiation and progression of bladder cancer.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%